From entrepreneurial cognition to entrepreneurial intention and behavior: The case of higher educational institutions in China - Chen, Su; Shen, Wenbin; Tan, Xinyu; Liu, Rongzhi (Frontiers in Psychology, 2022)
For graduates, entrepreneurship has been called "high quality employment" in China. Therefore, universities have paid more attention to entrepreneurship education, which is significant for entrepreneurial success. Based on the theory of “informed intentions” planned behavior and dual cognitive processing theory, this paper studies the relationship among entrepreneurial cognition, entrepreneurial intention, recognition perception of college entrepreneurship education, and entrepreneurial behavior from the perspective of mass innovation and mass entrepreneurship. The hypotheses are tested using a hierarchical linear regression model based on data from 786 valid questionnaires from more than 400 universities across China. This study finds that students’ entrepreneurial cognition positively affects their entrepreneurial behavior, that entrepreneurial intention plays a mediating role by positively strengthening the relationship between the two, and that the recognition perception of college entrepreneurship education strengthens the positive relationship between entrepreneurial intention and entrepreneurial behavior. The present research results provide a new perspective and framework for studying the entrepreneurial cognitive education of students, and they have certain practical significance for the reform of entrepreneurship education in Chinese universities.